The use of acute oxygen supplementation upon muscle tissue saturation during repeat sprint cycling - Porter, M. S.; Reed, K.; Jones, B. (Journal of Human Sport & Exercise, 2022)
This study examined performance and physiological responses (power output, tissue saturation index) to repeat sprint cycling with oxygen supplementation (O2Supp [fraction of inspired oxygen 1.00]). Fourteen amateur male cyclists took part. Two visits to the laboratory entailed; 15min relative intensity warm-up, 10min of passive recovery, followed by 10x15s repeated sprints, during which air inspired had FiO2 1.00 oxygen or normal air. Outcome measures include, mean power (W) and change in Tissue Saturation Index (DeltaTSI%). Repeated measures ANOVA were used to examine difference between conditions in mean power output. Paired samples t-tests were used to examine differences between conditions in DeltaTSI (%) and rate of muscle reoxygenation and deoxygenation (%/s). Mean power output was 4% higher in the oxygen condition compared to normoxia (p < .01). There was a significant positive correlation between power output and reoxygenation rate during O2Supp (r = 0.65, p = .04). No correlation was seen between power output and reoxygenation rate during normoxia (r = -0.30, p = .40). A significantly increased deoxy rate was seen in the O2Supp condition compared to normoxia (p = .05). Oxygen supplementation appears to elicit the greatest performance improvements in mean power, potentially facilitated by an increasing muscle reoxygenation rate. This evidences the utility of oxygen as an ergogenic aid to in cycling performance.